2008
DOI: 10.1016/j.vaccine.2008.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin rescues mice from lethal intra-nasal infections with virulent Francisella tularensis and induces immunity and production of protective antibody

Abstract: The ability to protect mice against respiratory infections with virulent Francisella tularensis has been problematic and the role of antibody-versus-cell-mediated immunity controversial. In this study, we tested the hypothesis that protective immunity can develop in mice that were given antibiotic therapy following infection via the respiratory tract with Francisella tularensis SCHU S4. We show that mice infected with a lethal dose of SCHU S4, via an intra-nasal challenge, could be protected with levofloxacin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 54 publications
1
53
1
1
Order By: Relevance
“…4B). This is in dramatic contrast to our previous findings that showed LEVO therapy initiated at 5 days postchallenge did not resolve lethal F. tularensis infection (21). Importantly, these increased survival times also allowed for successful initiation of LEVO treatment even 5 days after Schu 4 challenge (Fig.…”
Section: Time Course For Poly(i:c)-afforded Protection Against F Tulcontrasting
confidence: 82%
See 3 more Smart Citations
“…4B). This is in dramatic contrast to our previous findings that showed LEVO therapy initiated at 5 days postchallenge did not resolve lethal F. tularensis infection (21). Importantly, these increased survival times also allowed for successful initiation of LEVO treatment even 5 days after Schu 4 challenge (Fig.…”
Section: Time Course For Poly(i:c)-afforded Protection Against F Tulcontrasting
confidence: 82%
“…To determine whether poly(I:C) could extend the time before effective LEVO therapy initiation, mice were treated with poly(I:C) 1 h post-Schu 4 challenge and then, 5 days later, they were i.p. injected with 40 mg of LEVO/kg (21). This study also repeated groups of animals treated with poly(I:C), followed by Schu 4 infection, to confirm the previous results.…”
Section: Time Course For Poly(i:c)-afforded Protection Against F Tulsupporting
confidence: 80%
See 2 more Smart Citations
“…Klimpel et al also reported a similar finding using immune serum from mice cured of a lethal intranasal (i.n.) SCHU S4 infection with levofloxacin in a passive immunization model (27). Thus, the protective effects of antibodies appear not to be restricted only to low-virulence strains but may also contribute to the protection against highly virulent type A strains.…”
mentioning
confidence: 99%